Digital-Based Financial Management Capacity Building for BUMDes Mattuju in Pitue Village, Indonesia - Muhammad Fauzan Garantjang; Ade Ikhlas Amal Alam; Andi Iqra Pradipta Natsir; Muhammad Try Dharsana; Anissa Aulya Putri T. (Advances in Community Services Research, 2026)
Purpose: This Community Service Activity aims to strengthen the capacity of BUMDes Mattuju and village microbusiness actors in Pitue Village, Ma'rang Subdistrict, Pangkajene and Kepulauan Regency, in managing finances through simple digital recording, transparent reporting, and basic digital promotion. The program addresses the need for more orderly bookkeeping, stronger accountability, and data-informed decision-making in managing village-owned enterprises. Method: The activity used a participatory capacity-building approach through training, Focus Group Discussion (FGD), practical simulation, introduction to social media, simple website utilization, and mentoring. It involved BUMDes Mattuju, village microbusiness actors, village and subdistrict stakeholders, lecturers, and students of the 2025 Student Village Development Program of Universitas Hasanuddin. Results and Discussion: The program improved participants' awareness of structured financial records, introduced simple digital recording, and broadened their understanding of Facebook, Instagram, WhatsApp, and simple web-based channels for product visibility. It also produced training materials, brochures, seminar kits, certificates, documentation, and online media publications. Implication: The intervention strengthens BUMDes governance by positioning digital financial management as a practical tool for transparency, efficiency, and accountability. Continued mentoring is needed to make the introduced recording format a routine managerial practice, and the model can be replicated in other coastal and rural villages.